Catheter Ablation of Ventricular Tachycardia Guided by Substrate Electrical Inexcitability. (9th March 2021) - Bennett, Richard; Campbell, Timothy; De Silva, Kasun; Bhaskaran, Ashwin; Kumar, Saurabh
Abstract : Supplemental Digital Content is available in the text.